Analysis of motor competence and physical fitness in dancers: a pilot study - Daniela Alves; Filipe Manuel Clemente; Carla Gonçalves; Maria João Lagoa; Ana Filipa Silva (Termedia Publishing House, 2023)
Purpose The aim of this study was to characterize and compare the motor competence and physical fitness in dancers of different styles considering age, body mass index, and physical activity level (min/week). Methods Overall, 17 female dancers aged 13-31 years (18.00 ± 4.80) participated in this study. The sample was divided into 2 groups: (1) dancers who practised up to 3 styles ( n = 10); (2) dancers who practised 4 or more styles ( n = 7). The Fit School and Motor Competence Assessment test batteries were applied to analyse physical fitness and motor competence, respectively. All variables were tested for normal distribution by using the Shapiro-Wilk test. For continuous variables, the t -test was used and for nominal variables, the chi-square test was employed. For those that did not follow normal distribution, the Mann-Whitney U -test was applied. Results For either motor competence or physical fitness, the number of dance styles did not exert any influence. Furthermore, no significant differences were found for between-group comparisons. Conclusions The total group fell within the average reference values in all the physical fitness tests, with the exception of the 20-m multistage maximum shuttle run test. With regard to the number of dance styles practised, no differences between groups were observed for either motor competence or physical fitness.